Morphological study and new geographic records of opheliids and travisiid (Annelida: Polychaeta) from the Argentine Patagonian coast - Diez, María Emilia; Mohamed, Nadia; Rizzo, Alexandra E.; Cremonte, Florencia (Zootaxa, 2026)
Three species of polychaete were identified off the Patagonian coast, Argentina. These represent the first records in the studied locations. Two species of opheliids were identified, Armandia aff. loboi in Riacho San José (42° S) in the San José Gulf and Thoracophelia furcifera in Punta Marqués (45° S) in the San Jorge Gulf. One travisiid species, Travisia cf. olens, was found in Puerto Madryn, Nuevo Gulf (42° S). The present study provides detailed information of these species regarding the external morphology and some features of internal morphology. Further studies are necessary to clarify the identity of Armandia aff. loboi as it may represent a new species.